2024
DOI: 10.3390/atmos15020205
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Crop Water Stress Index (CWSI) for High Tunnel Greenhouse Tomatoes under Different Irrigation Levels

Sedat Boyaci,
Joanna Kocięcka,
Atilgan Atilgan
et al.

Abstract: An experiment was conducted to determine the effect of water stress on yield and various physiological parameters, including the crop water stress index for tomatoes in the Central Anatolian region of Turkey. For this purpose, the irrigation schedule used in this study includes 120%, 100%, 80%, and 60% (I120, I100, I80, I60) of evaporation from the gravimetrically. Water deficit was found to cause a stress effect in tomato plants, which was reflected in changes in plants’ morphological and pomological function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The pH of tomato juice is an important quality parameter that determines taste. In previous research, Lovelli et al [53] and Boyaci et al [46] reported that the difference between different irrigation levels and pH values was statistically significant (p < 0.01). Gutiérrez-Miceli et al [44] found that vermicompost applications statistically affected pH values in tomato cultivation compared to the control group without VC (p < 0.05).…”
Section: Quality Parameters Of the Tomatoesmentioning
confidence: 89%
See 4 more Smart Citations
“…The pH of tomato juice is an important quality parameter that determines taste. In previous research, Lovelli et al [53] and Boyaci et al [46] reported that the difference between different irrigation levels and pH values was statistically significant (p < 0.01). Gutiérrez-Miceli et al [44] found that vermicompost applications statistically affected pH values in tomato cultivation compared to the control group without VC (p < 0.05).…”
Section: Quality Parameters Of the Tomatoesmentioning
confidence: 89%
“…Colimba-Limaico et al [31] found that the values for stem diameter increased with increasing irrigation levels (80%, 100%, 120% and 140%). Boyacı et al [46] found that the difference in plant stem diameter between different irrigation levels (60%, 80%, 100% and 120%) was significant (p < 0.01). In this study, increasing irrigation levels and VC doses increased plant stem diameter.…”
Section: Morphological Properties Of Tomatoesmentioning
confidence: 98%
See 3 more Smart Citations